Changes in winter wheat (Triticum aestivum L.) phenotype in response to breeding for yield and in-furrow fertilizer - Maeoka, Rafael Eidi (Kansas State University, 2019)
The grain yield of winter wheat (Triticum aestivum L.) increased over time through plant breeding, and preliminary research suggested that yield response to fertilizer differs in modern versus historical genotypes. However, this response is not universal. We hypothesize selection for yield may have unintentionally modified the dynamics of nutrient uptake and partitioning in the plant. Thus, our objectives were to identify the key shifts in crop phenotype, in above-ground biomass and in dynamics of nutrient uptake and partitioning during vegetative and reproductive phases in response to selection for yield and to in-furrow fertilizer. Field experiments were conducted in four Kansas environments in a factorial trial combining eight winter wheat varieties released between 1920 and 2016, and two fertilizer practices (control versus 112 kg ha⁻¹ in-furrow 12-40-0-10-1). Grain yield and grain N-removal increased non-linearly with year of release (YOR), with greater increases between 1966 and 2000. In-furrow fertilizer increased yield in ~300 kg ha⁻¹ with no variety x fertility interactions. Grain protein concentration (GNC) related negatively to yield, and the residuals of this relationship were unaffected by YOR. Yield increase in semi-dwarf varieties were associated with shorter vegetative period and longer grain filling period, and more kernels m⁻² derived from more kernels head⁻¹. Historical varieties were taller, had thinner stems, and allocated more biomass to the stem than semi-dwarf varieties. At grain filling and maturity, shoot biomass was similar among varieties but semi-dwarf varieties allocated more dry matter to the kernels, suggesting that increases in yield derived from greater harvest index (HI) rather than greater biomass. Whole plant nutrient concentration negatively related to whole plant biomass and increased over decades for N, P, and S and decreased for K. In-furrow fertilizer increased the concentration of all nutrients. Grain-N, P, K, and S uptake increased from historical to semi-dwarf varieties; thus, nutrient HI increased with YOR, with greater increases between 1966 and 2000. Nutrient HI decreased with in-furrow fertilizer as the fertilizer increased biomass allocation to the vegetative tissues more than to the grain. Nutrient allocation rate to the head related positively to whole plant uptake rate, and YOR increased the head allocation rate for N, K, and S. There were positive and significant relationships between NHI and the HI of P, K, and S. Whole plant N uptake and P, K, and S uptake were also positively related, with ratios of 9.2, 1.1, and 15.4 for N:P, N:K, and N:S. Direct selection for grain yield modified the dynamics of nutrient uptake and partitioning over time, with semi-dwarf varieties allocating more N, P, K, and S to the grain. The ability of modern varieties to allocate more biomass and nutrients to the grain, coupled to an early maturity and longer grain filling period, increased grain yield and grain N-removal over time. However, increases in yield were greater than those in N-removal, reducing GNC. In-furrow fertilizer increased grain yield, biomass, and grain N, P, K, S uptake; nonetheless, the lack of variety x fertility interaction suggested variety response to fertility was similar.
Keywords: Triticum aestivum L.; Genetic progress; Yield components; Nutrient uptake; Nutrient partitioning